2018
DOI: 10.1016/j.joca.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in synovial fluid and serum concentrations of cartilage oligomeric matrix protein over 5 years after anterior cruciate ligament rupture: an exploratory analysis in the KANON trial

Abstract: The local process after an acute ACL injury generates increased SF COMP concentrations in the injured knee up to 5 years after injury. This response is not detected in serum. Discrepancies in associations between sCOMP measured by BioVendor and AnaMar immunoassays with other biomarkers indicate differences in detected COMP fragments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…It recruits principally monocytes and to a lesser extent, memory T cells and dendritic cells to sites of inflammation. CCL2 is expressed in the synovial sublining cells of OA joints, and has been found in synovial fluid of OA knee joints 8 , 9 and following acute traumatic injury 10 , 11 . Ccl2 is strongly and rapidly (<6 h) induced in whole joints upon surgical joint destabilisation in the mouse 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It recruits principally monocytes and to a lesser extent, memory T cells and dendritic cells to sites of inflammation. CCL2 is expressed in the synovial sublining cells of OA joints, and has been found in synovial fluid of OA knee joints 8 , 9 and following acute traumatic injury 10 , 11 . Ccl2 is strongly and rapidly (<6 h) induced in whole joints upon surgical joint destabilisation in the mouse 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal studies demonstrating release of COMP into the joint environment after injury 8,9 ; a number of studies have found that synovial fluid and/or serum COMP is increased with joint injury and/or the progression of OA (in both cross-sectional and longitudinal studies) 16,17,30 . It is also important to note that not all studies have demonstrated that COMP increase after joint injury and/or correlates with structural changes within the joint 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Daily calibration of the scanner employed a phantom spine containing composites of bone, fat and lean tissue. Participants were positioned in supine on the scanner bed according to the manufacturer's recommendations and instructed to remain as still as possible for the duration of the scan 16 . All procedures were consistent with the official positions of the International Society for Clinical Densitometry 26 .…”
Section: Fat Mass Indexmentioning
confidence: 99%
“…It is well known that the altered joint milieu in addition to cartilage damage and meniscal loss is associated with the development of osteoarthritis. [11][12][13] Some of those changes probably get relevant in the long run. 11 The disorder of collagen turnover following ACL-R has also been investigated.…”
Section: See Related Article On Page 996mentioning
confidence: 99%
“…[11][12][13] Some of those changes probably get relevant in the long run. 11 The disorder of collagen turnover following ACL-R has also been investigated. The study suggests that type II collagen degradation may be greater in the ACL-R joint compared with type II collagen synthesis at higher joint strain.…”
Section: See Related Article On Page 996mentioning
confidence: 99%